Role of Sugarcane Bagasse Ash in Developing Sustainable Engineered Cementitious Composites - Amin, Muhammad Nasir; Ashraf, Muhammad; Kumar, Rabinder; Khan, Kaffayatullah; Saqib, Daniyal; Ali, Syed Sajid; Khan, Sajidullah (Frontiers in Materials, 2020)
Sugarcane bagasse is an agricultural waste that can be transformed by incineration into a cement replacement material for various cementing purposes. This study investigated the role of finely ground bagasse ash (GBA) in producing engineered cementitious composites (ECCs) with the addition of polyvinyl alcohol (PVA) fibers. The main focus of this study was to develop a green ECC with higher strength capabilities (compressive, tensile and flexural) and greater tensile ductility. To develop this composite, GBA was added into ECC mixes at different proportions, i.e., 10, 20 and 30%. The proportions of PVA fibers and the water-to-binder ratio were kept constant. The results revealed that the ECC mix containing 10% GBA exhibited higher compressive strength compared to that of a control and the other ECC mixes. Furthermore, the tensile and flexural strengths of the ECCs exhibited patterns almost similar to that of compressive strength. Moreover, the deflection in the control mix was higher compared to that of the GBA-ECC mixes at an initial curing age. The ECC mix containing 10% GBA exhibited better ductile behavior among all the ECC mixes used in this study.